Development of Student Books Characterized by Indonesian Realistic Mathematics Education to Support Mathematics Problem Solving Ability - Hastuti, Intan Dwi; Ahyansyah, Ahyansyah; Mawaddah, Sukma; Sutarto, Sutarto (JTAM (Jurnal Teori dan Aplikasi Matematika), 2022)
This study aims to produce a student's book characterized by the Indonesian Realistic Mathematics Education Approach on fractional arithmetic operations material for grade V Elementary School that is valid, practical, and effective. This Research and Development uses the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The analysis phase consists of an analysis of student needs and curriculum analysis. At the design stage, namely the preparation of a map of student book needs, determining the structure of student books and making research instruments. At the development stage, namely preparing student books and validating student books to experts. The implementation phase includes teaching experiments to 3 students (one on one), small groups (small groups) and field tests. Then, at the evaluation stage includes the assessment of student books with teachers and students. This study uses the Indonesian Realistic Mathematics Approachin the matter of fractional arithmetic operations. The results showed that the average percentage of student book validity according to experts was 79.4% with the assessment criteria being valid or could be used with revisions. Meanwhile, the average percentage of practicality of student books according to students is 75.7% with the assessment criteria being practical or can be used with revisions. Meanwhile, the average percentage of the effectiveness of student books according to students is 77.5% with the assessment criteria being effective in supporting students' mathematical problem solving abilities.